2018
DOI: 10.29313/mimbar.v34i2.2914
|View full text |Cite
|
Sign up to set email alerts
|

Financial Literacy Model at Micro Small Medium Entreprise (MSMEs)

Abstract: Financial literacy level of MSMEs (Micro, Small, and Medium Enterprises) is only 15.68% and majority of the actors are unbanked. The level of MSMEs actors’ financial literacy is important in business sustainability. This study aims to measure level of MSMEs financial literacy and determine its correlation with demographic and economic variables as well as designing models to increase the literacy.Results show that 51 (25.5%) actors of  MSMEs  have low literacy level, 105 (52.5%) have moderate level, and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
6
0
2
Order By: Relevance
“…In order to have good financial management, MSMEs must learn to properly understand the basic knowledge of finance, and the specific knowledge of banking, investment and insurance. This is strengthened by the study results in 2013 found that the level of financial literacy of MSME was still very low at only 15.68% (Widiyati et al, 2018). Thus, the results of the OJK survey imply that the knowledge of finance of the MSME actors must be improved.…”
Section: Introductionmentioning
confidence: 94%
“…In order to have good financial management, MSMEs must learn to properly understand the basic knowledge of finance, and the specific knowledge of banking, investment and insurance. This is strengthened by the study results in 2013 found that the level of financial literacy of MSME was still very low at only 15.68% (Widiyati et al, 2018). Thus, the results of the OJK survey imply that the knowledge of finance of the MSME actors must be improved.…”
Section: Introductionmentioning
confidence: 94%
“…Individuals who have a financial attitude can be seen from how their personalities carry out good financial management practices for their future. Based on research by Widiyati et al, (2018) shows that good habits in money management lead to better literacy results. When financial attitudes improve, people's financial management becomes correct.…”
Section: Financial Attitude To the Financial Literacymentioning
confidence: 99%
“…MSME procedures for obtaining bank funding are complicated. The financial literacy level of MSMEs (Micro, Small, and Medium Enterprises) is only 15.68% and a majority of the actors are unbanked (Widiyati et al, 2018) The distribution system is hampered since the COVID 19 pandemics. Decreased Turnover of MSMEs due to covid-a9 is very significant Since its appearance at the end of 2019 (Amri, 2020).…”
Section: The Threats Faced By Msmes In Their Developmentmentioning
confidence: 99%